Incidence of Antidrug Antibodies in Rheumatoid Arthritis Patients From Argentina Treated With Adalimumab, Etanercept, or Infliximab in a Real-World Setting. Issue 4 (June 2018) - Maid, Pablo J.; Xavier, Ricardo; Real, Rosa M.; Pedersen, Ron; Shen, Qi; Marshall, Lisa; Solano, Gaston; Borlenghi, Cecilia Elena; Hidalgo, Rodolfo Pardo
Abstract : Background: Biologic agents may induce immune responses that could impact drug action. Objectives: The aims of this study were to assess antidrug antibodies (ADAs) in patients with rheumatoid arthritis (RA) from Argentina treated with etanercept, adalimumab, or infliximab at a single visit and correlate it with efficacy outcomes. Methods: In this subset analysis of a noninterventional, multinational, cross-sectional study (NCT01981473), adult patients with RA treated continuously for 6 to 24 months with etanercept, adalimumab, or infliximab were evaluated for ADAs and trough drug concentrations of 2 days or less prior to the next scheduled dose. Efficacy measurements included Disease Activity Score based on a 28-joint count–erythrocyte sedimentation rate, low disease activity, and Health Assessment Questionnaire—Disability Index. Targeted medical history of injection site/infusion reactions, serum sickness, and thromboembolic events were reported. Results: Baseline demographics, disease characteristics, and duration of treatment of the 119 patients (etanercept: n = 54, adalimumab: n = 52, infliximab: n = 13) were similar across all groups. No etanercept-treated patient tested positive for ADAs compared with 19 (36.5%) of 52 patients and 4 (30.8%) of 13 patients treated with adalimumab and infliximab, respectively. In adalimumab- and infliximab-treated patients, ADA presence correlated negatively with trough drug levels. A greater proportion of ADA-negative patients achieved Health Assessment Questionnaire—Disability Index of 0.5 or less and had better composite efficacy measures compared with ADA-positive patients. The rate of targeted medical events reported was low. Conclusions: In this subset analysis, RA patients from Argentina treated with adalimumab or infliximab, but not etanercept, tested positive for ADAs. Antidrug antibody–negative patients showed a tendency toward better clinical outcomes compared with ADA-positive patients.